(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Underfunded schools face challenges such as inadequate infrastructure and limited resources, which affect education quality. This study explored the leadership practices of principals in these environments through in-depth interviews with seven principals. Findings indicated that they used transformational leadership, resource mobilization, and community engagement to mitigate financial constraints. The study recommended increasing professional development for principals and enhancing policy support to improve leadership effectiveness in underfunded schools.